Taxonomic notes and typification of some Habenaria species in the Pan-Himalaya - Pandey, Tirtha Raj; Jin, Xiao-Hua (Phytotaxa, 2021)
Habenaria Willd. (1805: 44) is represented by more than 35 species in the Pan-Himalaya (Chen & Cribb 2009, Pearce & Cribb 2002, Hooker 1890). As part of the ongoing revision work on the Pan-Himalayan Habenaria, some species of this species-rich genus are typified for nomenclatural clarity. Several species belonging to this genus have a long collection and taxonomic history and therefore pose difficulty in locating the original materials partly because either they were dispersed over various herbaria or were often catalogued under the disguise of different names. Through the critical examination of all the putative original materials—herbarium specimens and corresponding protologues, here we propose lectotypes of three species.